Influence of temperature-humidity index on conception rate of Nelore embryos produced in vitro in northern Brazil - Cordeiro, A. L.L.; Satrapa, R. A.; Gregianini, H. A.G.; Gregianini, J. T.F.; Maia, G. F.N.; Landim-Alvarenga, F. C. [UNESP] (Springer Nature, 2020)
Considering the high temperatures that the tropical climate provides to most of Brazil and the effects of thermal stress on reproductive processes, the objective of the present study was to analyze, in the warmer months of 2016, conception rates of Nelore bovine embryos in Acre state. For this purpose, oocytes were aspirated (ultrasound-guided follicular aspiration), matured, fertilized with Nelore bull semen, cultured for 6 days, and then the embryos were transferred to crossbred recipients. Pregnancy diagnosis was performed 30 and 60 days after embryo transfer. Meteorological data were obtained at www.inmet.gov.br to generate temperature-humidity index (THI). The data from the conception rates and periods of the year were submitted to the chi-square test at 5% probability to verify independence. Regression analysis was used to verify the relationship between THI and gestation rate. There was a strong relationship between conception rates and THI values, verified by an increase in conception rates as THI values were reduced and a decrease when THI reached the highest value. Our findings demonstrated a negative effect of heat stress in conception rates of crossbred cows in northern Brazil.
Keywords: Blastocyst; IVP; Oocyte; Pregnancy rate; THI